The Effects of Receptor Activator of NF-κB Ligand-Binding Peptides on Bone Resorption and Bone Formation - Rashed, Fatma; Kamijyo, Shingo; Shimizu, Yuri; Hirohashi, Yuna; Khan, Masud; Sugamori, Yasutaka; Murali, Ramachandran; Aoki, Kazuhiro (Frontiers in Cell and Developmental Biology, 2021)
Receptor activator of NF-κB ligand (RANKL)-binding peptides inhibit bone resorption and were recently shown to activate bone formation. The stimulatory mechanism underlying bone formation associated with these peptides was explained as RANKL-reverse signaling, wherein RANKL molecules on osteoblasts work as receptors to stimulate osteoblast differentiation. However, why RANKL-binding peptides stimulate osteoblast differentiation while osteoprotegerin (OPG), which is well known to bind to RANKL, cannot activate osteoblast differentiation has remained unclear. In this mini-review, we introduce three main issues: (1) The inhibitory effects of two RANKL-binding peptides (W9 and OP3-4) on bone resorption; (2) The stimulatory effects of the RANKL-binding peptides on osteoblast differentiation; and (3) The accumulation and membrane clustering of RANKL molecules at the cell surface of osteoblasts as a potential molecular switch stimulating osteoblast differentiation by RANKL-binding peptides.